Factors associated with meeting homosexual partners at fixed offline locations among MSM recruited through the internet: A cross-sectional survey - Weiyong Chen; Zhongrong Yang; Xing Wang; Weiwei Wang (PLoS ONE, 2025)
Objective This study aimed to investigate the demographic characteristics of Men who have Sex with Men (MSM) recruited online and identify the factorsassociated with meeting homosexual partners at fixed offline locations. Methods Univariate and multivariate logistic regression analyses were used to examine the factors that influenced their meeting up with homosexual partners at fixed offline locations. Results A total of 604 MSM were included, with 133 participants (22.02%) meeting homosexual partners at fixed offline locations. Multivariate logistic regression analysis showed that participantswho were willing to engage in commercial sex, engage in behaviors such as alcohol consumption, drug use, or aphrodisiac use during homosexual activities, and hadused HIVPre-Exposure Prophylaxis (PrEP) in the last six months were more likely to meet homosexual partners at fixed offline locations. Conclusions The proportion of participants meeting homosexual partners at fixed offline locations was relatively high, emphasizing the need to increase education and awareness among MSM to reduce relatedbehaviors during homosexual activities. Further promotion of the proper use of PrEP and avoidance of commercial sex are essential for lowering the risk of HIV infection among this population.